Phosphorylation Status of Tyrosine 78 Residue Regulates the Nuclear Export and Ubiquitination of Influenza A Virus Nucleoprotein - Cui, Liang; Zheng, Weinan; Li, Minghui; Bai, Xiaoyuan; Yang, Wenxian; Li, Jing; Fan, Wenhui; Gao, George Fu; Sun, Lei; Liu, Wenjun (Frontiers in Microbiology, 2019)
Phosphorylation and dephosphorylation of nucleoprotein (NP) play significant roles in the life cycle of influenza A virus (IAV), and the biological functions of each phosphorylation site on NP are not exactly the same in controlling viral replication. Here, we identified tyrosine 78 residue (Y78) of NP as a novel phosphorylation site by mass spectrometry. Y78 is highly conserved, and the constant NP phosphorylation mimicked by Y78E delayed NP nuclear export through reducing the binding of NP to the cellular export receptor CRM1, and impaired virus growth. Furthermore, the tyrosine kinase inhibitors Dasatinib and AG490 reduced Y78 phosphorylation and accelerated NP nuclear export, suggesting that the Janus and Src kinases-catalyzed Y78 phosphorylation regulated NP nuclear export during viral replication. More importantly, we found that the NP phosphorylation could suppress NP ubiquitination via weakening the interaction between NP and E3 ubiquitin ligase TRIM22, which demonstrated a cross-talk between the phosphorylation and ubiquitination of NP. This study suggests that the phosphorylation status of Y78 regulates IAV replication by inhibiting the nuclear export and ubiquitination of NP. Overall, these findings shed new light on the biological roles of NP phosphorylation, especially its negative role in NP ubiquitination.